PERCEPTION OF SCIENTIFIC AND TRANSVERSAL COMPETENCIES IN NURSING STUDENTS: A COMPARATIVE ANALYSIS BETWEEN UNIVERSITY COHORTS - Bernés, Salvador Ruiz; Quiroz, Alejandrina Montes; Padilla, Hanna Kasandra Ruiz; Pimienta, Diana Pérez; Fonseca, Aimée Argüero; de Ávila, Marcela Rábago; Lima, Carmen Julia Cruz; Saucedo, Paloma Michelle Pérez; Becerra, Angélica Cristina Jacobo; Ramírez, Sheyla Casandra Sánchez (Seven Editora, 2026)
In higher education in health sciences, the development of scientific and transversal competencies is essential for training professionals capable of critically analyzing evidence and applying it in clinical practice. The aim of the study was to compare the perception of scientific and transversal competencies among nursing students between the periods 2019 and 2025, in order to identify possible differences associated with the educational contexts in which their training took place. Materials and Methods: A quantitative, non-experimental, cross-sectional, and comparative study was conducted among undergraduate nursing students at a public university in Nayarit, Mexico. The sample consisted of 331 students selected through non-probabilistic convenience sampling. Data were collected using a questionnaire based on an ad hoc instrument and analyzed using descriptive and inferential statistics, employing χ² and Mann-Whitney U tests (p < 0.05). Results: The findings showed that transversal competencies were mainly at intermediate levels of development, highlighting teamwork and ethical and social commitment. In contrast, scientific competencies showed lower levels of perceived mastery, particularly in methodological skills. Conclusions: The findings highlight the need to strengthen research training and to promote pedagogical strategies aimed at critical thinking and scientific literacy among nursing students.